Análise compartiva da evolução de miRNAs utilizando insetos como modelo - Karla Pollyanna Vieira de Oliveira (2016)
MicroRNAs (miRNAs) are a small non-coding RNA class discovered in 1993. These sequences originate from the endogenous precursors, which are processed into small RNAs ranging size from 20 to 24 nt. MiRNAs are conserved in eukaryotes and they are important gene regulators. Despite their importance and the sequence conservation among species, other miRNAs’ features conservation remains unclear since there are no studies of such aspects. To answer this question, we generated small RNAs libraries – derived from three dipteran insects whose evolutionary distance is approximately 250 million years ago. The libraries were sequenced, and the miRNAs of each organism were analyzed according to species conservation, sequence, size profile, 5' homogeneity, genomic origin, precursor origin, and preferably base. Overall, it was observed high conservation of miRNAs between the three dipteran insects not only in terms of their sequences, but also in terms of all the other features. However, when we analyzed miRNAs that were found in only one specie, it was observed a higher divergence of miRNAs patterns than observed in conserved miRNAs. These observations can be explained by the time of miRNAs evolution. Conserved miRNAs are evolutionarily older than non-conserved miRNAs and they have been naturally selected. In contrast, the miRNA-specific species were the most recent and therefore have not been selected. Thus, these results suggest that the evolutionary pressure suffered by miRNAs is reflected not only in their sequence, but also in other intrinsic characteristics probably linked to its overall structure that determines how it is their biogenesis.